Implementation of Internal Mixed Signal ESD Protection onto RFID Transponder IC - Khaw, M. K.; Mohd-Yasin, F.; Teh, Y. K.; Reaz, M B.I. (2006)
Radio Frequency Identification (RFID) has become an important wireless data communication tool in recent years. As much as we want to ensure data integrity and the robustness of the RFID transponder, Electrostatic Discharge (ESD) influence on the transponder can jeopardize it. Current practice put the ESD protection in the package. However at pad level, the ESD protection is usually small dimensioned to reduce input capacitance. Hence extra ESD protection co-constructed at internal circuit VDD-VSS rail is necessary in advanced process due to thinner gate oxide. In this paper, we have developed an internal ESD protection circuit and implemented it in our previously developed 13.56MHz RFID transponder employing TSMC 0.18 mu m process. The circuit has a capability to sustain 2-KV of HBM positive mode ESD voltage, which is suitable for RFID applications. The additional power consumption for the clamp circuit is only 15.12nW.